Análise SWOT da formação de Medicina Geral e Familiar em Angola - Clara Tidiane Lucas da Silva Fernandes (2024)
Primary health care (CSP) play a key role in any country's health system, acting as the first line of defense in prevention, promotion and treatment of disease. In Angola, a developing country with an evolving healthcare system, CSPs are especially crucial to meet the health needs of the population, and significantly challenging for the scarcity of resources and lack of proper infrastructure.Primary health care play a role crucial in the development of the specialty of a family physician, emphasizing the importance of family physicians as key clinicians in providing comprehensive and patient-centric care. Objectives: General: Assessing forces and weaknesses in the General and Family Medicine training program at, Angola, aiming to identify areas of improvement and promote the quality of medical education in this specialty. Specifics: 1. Identifying major strength areas in the training program including educational, institutional, faculty quality and effective pedagogical approaches. 2. Analyze major areas of weakness in the training program, including gaps in educational infrastructure, challenges in student supervision and guidance, and limitations in student hands-on exposure. 3. Assessment of FGM training by Angola's perspective of FGM interns and physicians. Methods: Study Type: Observational, Descriptive, Transverse. Site and Study Period: Angola, in the period of April à June 2014.Population and sample of the study: Specialists, teachers, monitors, interns and health professionals involved in the training of General and Family Medicine in Angola, with a total of 584 participants. Sources of Information: Structured Questionnaire. Information collection processes and data treatment: application of an electronic questionnaire on Google forms emailed and/or Whatsapp to participants. Statistical Analysis: Data was organized in Excel® Plating, Descriptive Analysis of the Study Variables in the SPSS® Program Variables Results: The sample comprises a total of 584 participants, 357 (61.1%) female, 227 (38.9%) male, with a mean age of 40.6 years. Angolans 466 (79.8%), Luanda being the province with the highest number of residents 130 (22.3%) and physicians in the FGM specialty. At the national level the specialty of MGF has 158 (27.1) experts and 401 (68.7%) non-experts. Conclusion: Analyse SWOT: forces: The positive assessment on the state of specialty and country level training. Weakness: Weak quality to access to teaching materials and resources. Opportunities: The interest of the specialty in health ministry and collaboration with the ministry of territory for best organization and spread of the specialty nationally Threats: Best working and teaching conditions. Keywords: training quality, primary health care, analyze swot.